The Role of Body-Related and Environmental Sources of Knowledge in the Construction of Different Conceptual Categories - Guido, Gainotti (Frontiers in Psychology, 2012)
Controversies exist about: (a) the relationships between perceptual and conceptual activities and (b) the format and neuro-anatomical substrates of concepts. Some authors maintain that concepts are represented in the brain in an abstract manner, totally unrelated to the sensory-motor functions of the brain, whereas other authors argue that concepts are represented in the same format in which they have been constructed by the sensory-motor system. The present paper will survey two groups of investigations that play in favour of the second view, devoting particular attention to the role of body movements and somatosensory inputs in the representation of artefacts and, respectively, of visual and other perceptual sources of knowledge in the construction of biological categories. The first group of investigations is represented by studies that have tried to assess the weight that various kinds of information play in the representation of different conceptual categories. This was made by asking normal subjects to rate their subjective evaluation of the role that various perceptual, motor and encyclopaedic sources of knowledge could have in the construction of different semantic categories. The second group of studies deals with research concerning the neuro-anatomical correlates of various types of categorical disorders, because these investigations have shown that the cortical areas damaged in patients with a disorder selectively affecting a given category play a critical role in processing information that have mainly contributed to the construction of the affected category. Both lines of research suggest that body movements and somatosensory information play a major role in the representation of actions and of artefacts mainly known through manipulations and other actions, whereas visual and other perceptual information play a dominant role in the representation of animals and other living entities.